Comparison of The Performance of Proton Exchange Membrane Fuel Cell (PEMFC) Electrodes with Different Carbon Powder Content and Methods of Manufacture - D. Rohendi; E.H. Majlan; A.B. Mohamad; L.K. Shyuan; J. Raharjo (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Abstract: Carbon powder in the gas diffusion layer (GDL) contained in the membrane electrode assembly (MEA) has an important role in the flow of electrons and reactant gas. Meanwhile, the method of making the electrode is one of the many studies conducted to determine the most appropriate method to use. Comparative study of the performance of proton exchange membrane fuel cell (PEMFC) electrodes with different carbon powder content (vulcan XC-72) in the GDL and  methods of manufacture of the electrode between casting and spraying method has been carried out. The spraying method consists of one layer and three layer of catalyst layer (CL). The content of carbon powder in the GDL as much as 3 mg cm-2 has a better performance compared to 1.5 mg cm-2 with an increase of 177.78% current density at 0.6 V. Meanwhile, the manufacture of CL with three-layer spraying method has better performance compared with one-layer spraying and casting method.Key words: casting method, spraying method, catalyst layer (CL), GDL.Abstrak (Indonesian): Serbuk karbon pada lapisan difusi gas (LDG) yang menyusun elektroda membran memiliki peran penting dalam mengatur aliran elektron dan gas reaktan. Pada sisi lain metoda pembuatan elektroda adalah salah satu dari banyak studi yang dilakukan untuk menentukan metoda yang paling sesuai yang dapat dikerjakan. Telah dikerjakan studi komparatif kinerja membran penukar proton pada elektroda sel bahan bakar dengan kandungan serbuk karbon (vulcan XC-72) dalam LDG yang bervariasi dan studi komparasi metoda pembuatan elektroda secara tuang dan semprot. Metoda semprot dikerjakan dalam dua variasi yakni pembuatan lapisan katalis (LK) satu dan tiga lapisan. Kandungan serbuk karbon dalam LDG hingga 3 mg cm-2 memiliki kinerja lebih baik dibanding 1,5 mg cm-2 dengan peningkatan kerapatan arus 17,78% pada 0,6 V. Pembuatan LK dengan metoda semprot tiga lapisan memperlihatkan kinerja terbaik dibanding metoda semprot satu lapisan dan metoda tuang.Kata kunci: metode casting, metode spraying, layer katalis, GDL